1986
DOI: 10.4039/ent118589-6
|View full text |Cite
|
Sign up to set email alerts
|

CONE AND SEED INSECTS OF TAMARACK, LARIX LARICINA (DU ROI) K. KOCH, AND ATTEMPTS TO CONTROL DAMAGE USING CHEMICAL INSECTICIDES

Abstract: An investigation of the insects that damage cones (megasporangiate strobili) and seeds of tamarack [Larix laricina (Du Roi) K. Koch] in New Brunswick was undertaken. During two growing seasons (1982 and 1983) cones were removed from natural and planted stands of tamarack on a weekly basis. These cones were dissected, the nature and amount of insect damage recorded, and insect habits documented. Efforts were made to rear to adults any destructive insects encountered in order to identify them and to isolate para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 3 publications
4
7
0
Order By: Relevance
“…These estimates of egg developmental time are similar to those reported previously for the S. laricislviaria complex (Amirault and Brown 1986;Chau 1993) and for other Strobilomyia spp., which range from 4 to 15 days (Tripp and Hedlin 1956;Michelsen 1988;Yao et al 1991). These estimates of egg developmental time are similar to those reported previously for the S. laricislviaria complex (Amirault and Brown 1986;Chau 1993) and for other Strobilomyia spp., which range from 4 to 15 days (Tripp and Hedlin 1956;Michelsen 1988;Yao et al 1991).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These estimates of egg developmental time are similar to those reported previously for the S. laricislviaria complex (Amirault and Brown 1986;Chau 1993) and for other Strobilomyia spp., which range from 4 to 15 days (Tripp and Hedlin 1956;Michelsen 1988;Yao et al 1991). These estimates of egg developmental time are similar to those reported previously for the S. laricislviaria complex (Amirault and Brown 1986;Chau 1993) and for other Strobilomyia spp., which range from 4 to 15 days (Tripp and Hedlin 1956;Michelsen 1988;Yao et al 1991).…”
Section: Discussionsupporting
confidence: 90%
“…Densities of larch cone maggots vary widely, however, and depend on the size of cone crops and the presence of other cone feeders (Amirault 1984;Eavy 1987;Roques 1988). Spruce budworm, Choristoneura fumiferana (Clemens), which caused heavy damage at the same time as cone maggots in other studies (Amirault 1984;Eavy 1987), was not present at our study site and cecidomyiids were found only after larvae of S. laricis and S. viaria had completed development. Strobilomyia viaria preferred unoccupied cones over those occupied by either S. viaria or S. laricis, suggesting that the largest interspecific influence on larch cone maggots in our study may have been by S. laricis on S. viaria.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Factors affecting oviposition site selection have received little attention in cone and seed insects in general (Miller & Borden, 1984;Mattson, 1986;Rappaport & Roques, 1991;Turgeon et al, 1994) and in Strobilomyia species in particular (Roques, 1988). Several authors have noted that S. laricis and S. viaria tend to lay one egg per cone (Amirault, 1984;Turgeon, 1989;Chau, 1993;McClure et al, 1996), which suggests that females probably recognize and avoid previously occupied oviposition sites when seed cones are abundant. When seed cones are limited however, Strobilomyia spp.…”
Section: Introductionmentioning
confidence: 99%